2011
DOI: 10.1177/009286151104500307
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Incidence, Causes, and Repercussions of Protocol Amendments

Abstract: Measuring the Incidence, Causes, and Repercussions of Protocol Amendments Drug development companies frequently amend finalized clinical trial protocols. Yet the incidence, causes, and impact of protocol amendments have never been quantified. Tufts Center for the Study of Drug Development (Tufts CSDD) conducted a study, in collaboration with 17 large and midsized pharmaceutical and biotechnology companies, examining more than 3,400 clinical trial protocols across development phases and therapeutic areas. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 1 publication
0
74
0
3
Order By: Relevance
“…The EHR4CR platform also enables the identification of eligible patients in relation to the clinical trials' inclusion and exclusion criteria in order to ensure their timely recruitment, as well as efficient clinical data exchange for facilitating clinical trial execution and SAE reporting. Accordingly, and as reported by Kalra et al, EHR4CR solutions are expected to deliver important benefits [5], such as improved clinical study planning, reduced number of protocol amendments (the cost of one protocol amendment being estimated at more than €400,000 (USD 450,000), with Phase III trials exceeding on average 3.5 amendments per trial [14,15]), reduced administrative burden, better patient and investigational site targeting, faster patient recruitment, seamless study conduct, reduction in clinical research actual person-time and costs, reduced clinical trial cycle time, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The EHR4CR platform also enables the identification of eligible patients in relation to the clinical trials' inclusion and exclusion criteria in order to ensure their timely recruitment, as well as efficient clinical data exchange for facilitating clinical trial execution and SAE reporting. Accordingly, and as reported by Kalra et al, EHR4CR solutions are expected to deliver important benefits [5], such as improved clinical study planning, reduced number of protocol amendments (the cost of one protocol amendment being estimated at more than €400,000 (USD 450,000), with Phase III trials exceeding on average 3.5 amendments per trial [14,15]), reduced administrative burden, better patient and investigational site targeting, faster patient recruitment, seamless study conduct, reduction in clinical research actual person-time and costs, reduced clinical trial cycle time, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Given that ClinGov has moved towards requiring inclusion of results, CCT may move in a similar direction, in which case some of the headings in the database could be used. l Make comparisons with other research, such as the cost casemix study of RCTs in the USA 132 and the analysis of cohorts of RCTs (as in the Cochrane Review by Djulbegovic et al…”
Section: Further Research/implementationmentioning
confidence: 99%
“…132 This work, being carried out for NIH in the USA using a portfolio of commercially funded trials, should be monitored and compared.…”
Section: Recommendations For the Future Metadata Databasementioning
confidence: 99%
“…Tufts CSDD found that one out of every four (24.7%) procedures performed in Phase III protocols supported tertiary and exploratory objectives and end points. The average cost to administer procedures supporting these 'Non-Core' objectives and end points represented 18% of the entire study budget, or $1.7 million per Phase III protocol [10]. This figure grossly underestimates the total cost of performing less essential procedures because it excludes all indirect costs for personnel and infrastructure required to capture, monitor, clean, analyze, manage and store extraneous protocol data and it does not begin to estimate the unnecessary risk to which patients may be exposed.…”
mentioning
confidence: 99%
“…Tufts CSDD found that complex protocols are amended on an average of 2.3-times at a direct cost of over $1 million per protocol and 4 months of incremental time to resolve. The implementation of amendments is highly disruptive causing significant unplanned expense and delays for research sponsors and unexpected burden for investigative sites [10].…”
mentioning
confidence: 99%